The role of in-person electronic accounting education in improving the performance level of accounting department graduates Case study on Omar Al-Mukhtar University (Economic studies journal, 2021)
AbstractThis study aimed to measure the role of electronic accounting education in a physical presence in improving the performance of graduates of the Accounting Department at Omar Al-Mukhtar University. The sample was chosen randomly to include the current faculty members in the accounting departments at Omar Al-Mukhtar University and its branches of 52 faculty members and as a result of the laws and The unified administrative regulations in the Libyan environment, which are organized by the Ministry of Higher Education in Libyan universities, and the performance of faculty members in all Libyan universities is identical. The study is that they have a good level of know-how and knowledge in the use of information technology, which means that there are challenges facing the use of electronic accounting education at Omar Al-Mukhtar University.       The participants also positively affirmed that the use of electronic accounting education in presence works to reduce the gap between the requirements of the labor market and university education through the development of academic courses in the accounting departments and raises the level of performance of graduates of the accounting department in a manner that suits the requirements of the accounting profession in the labor market because This greatly helps them to develop their scientific skills and abilities in using information technology in the accounting profession.
Keywords: university education; electronic accounting education; graduates of the accounting department; accounting departments at Omar Al-Mukhtar University